Agile HR: Adapting Human Resource Practices to Rapid Business Changes - Lusia Nargis; Brastoro Brastoro; Muhammad Fuad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In today's rapidly evolving business landscape, organizations face the challenge of adapting to dynamic changes while maintaining high levels of employee performance and engagement. This study investigates the relationships among Agile HR Practices, Business Changes, Employee Engagement, and Employee Performance within the context of PT. Jimmulya. Using a nonrandom sampling technique, data was collected from 90 employees and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that Agile HR Practices significantly influence both Employee Engagement and Employee Performance, highlighting the importance of flexible HR strategies in fostering a highly engaged workforce and driving improved performance outcomes. Additionally, Employee Engagement was found to mediate the relationship between Agile HR Practices and Employee Performance. However, the indirect effect of Business Changes on Employee Performance through Employee Engagement was non-significant, suggesting the need for further exploration of the complex dynamics between HR practices, business changes, employee engagement, and performance. These findings provide valuable insights for organizations seeking to enhance their HR strategies and navigate the challenges of dynamic business environments effectively.